Perchlorate‐Driven Combustion of Organic Matter During Pyrolysis‐Gas Chromatography‐Mass Spectrometry: Implications for Organic Matter Detection on Earth and Mars. Issue 7 (26th July 2018) - Royle, Samuel H.; Oberlin, Elizabeth; Watson, Jonathan S.; Montgomery, Wren; Kounaves, Samuel P.; Sephton, Mark A.
Abstract: The search for life on Mars targets the detection of organic matter from extant or extinct organisms. Current protocols use thermal extraction procedures to transfer organic matter to mass spectrometer detectors. Oxidizing minerals on Mars, such as perchlorate, interfere with organic detection by thermal extraction. Thermal decomposition of perchlorate releases oxygen, which promotes combustion of organic carbon. We have assessed the minimum mass ratio of organic carbon to perchlorate required to detect organic matter by thermal extraction and mass spectrometry. Locations on Mars with organic carbon to perchlorate ratios above 4.7–9.6 should be targeted. Because habitability is enhanced by the presence of liquid water and because perchlorate is a water‐soluble salt, locations on Mars with evidence of past or recent liquid water are high priority targets. Plain Language Summary: Missions to Mars look for evidence of organic molecules using thermal extraction techniques. Certain minerals on the Martian surface, such as perchlorate salts, break down during heating, releasing oxygen and causing the combustion of any organic matter, which may have been present. In this event organic carbon is lost to analysis as CO and CO2 . We used the ratio of CO: CO2 produced as a proxy for the completeness of combustion when various ratios of organic matter and perchlorate where thermally decomposed together. This allowed us to find a minimum organic carbon: perchlorate mass ratio (~5 times) for the survival of organic molecules. Carbon monoxide can only be produced if there is an excess of carbon to oxygen, which could enable the survival of unoxidized organic molecules for their subsequent detection. Applying these findings to Mars suggests that we would not expect to be able to detect organic molecules in average Martian soil. Consequently, future life detection missions to Mars must search for areas that exceed this ratio, either by having more organic matter or less perchlorate, and locations with evidence of recent water activity or in the subsurface are most likely to fulfill both of these criteria. Key Points: CO:CO2 response during thermal decomposition of organic matter with perchlorate is a proxy for completeness of combustion There needs to be approximately 5 times as much organic matter than perchlorate in samples for its detection by thermal decomposition techniques Future life detection missions will need to look for sites that improve the organic matter:perchlorate ratio compared to the average Martian regolith